Marriage able ages & penalization on early marriages in Pakistan: a critical analysis in the light of Islamic law - Muhammad Haroon; Muhammad Yousuf (jihat-ul-islam, 2023)
The fixation of the marriageable age and penalization on the early marriages have a significant opposition to Islamic Laws, which is the reason for the novel issues in society. This article analysis the subject considering the Islamic Laws. It addresses the main question that whether the law regarding the fixation of the marriageable age and penalization on the early marriages in Pakistan comply with Islamic Law? For this purpose, the laws of Pakistan, especially, and International Laws and other jurisdictions, generally, have been reviewed to highlight the gaps and disparities. The current findings show that related law on penalization and the fixation of the marriageable age is inadequate and is based on ancient Indian laws, which does not comply with Islamic Law. It concludes that Pakistan needs an amendment in the fixation of marriageable age under Islamic Law. These findings aim to help lawmakers to amend practicable preparedness strategies. The doctrinal legal research methodology has been followed. It adopts critical and analytical method along with qualitative conduct of the research.